PATHWAYS TO STRENGTHENING THE SUSTAINABILITY OF INTENSIVE OLIVE FARMS IN ALGERIA - Amrouni Sais Haoua*,**; Benziouche Salah Eddine*; Merrouchi Lounes* (Natural Resources and Sustainable Development)
This article explores ways of enhancing the sustainability of intensive olive farms in Algeria, with a particular focus on the semi-arid wilaya of Djelfa. The study, carried out on a sample of 57 olive farms, uses the Indicators of Farm Sustainability (IDEA) method to assess sustainability through its agro-ecological, socio-territorial and economic dimensions. The results show three typologies of farms, distinguished by variable performance in each of the sustainability dimensions. The best results were obtained by cluster 2, with respectively 64.81±6.92 for agroecological sustainability, 41.13±6.99 for socio-territorial sustainability and 62.81±7.48 for economic sustainability. The economically viable